2020
DOI: 10.7150/ijms.43030
|View full text |Cite
|
Sign up to set email alerts
|

Association of Human Papillomavirus Type 16 Long Control Region Variations with Cervical Cancer in a Han Chinese Population

Abstract: Objective: High-risk human papillomavirus (HPV) E6 and E7 proteins are the major oncoproteins involved in the tumorigenesis of cervical cancer. The long control region (LCR) in HPV plays an important role in regulating the expression of the E6 and E7 oncogenes. In the current study, we investigated the association of HPV16 LCR variations with cervical cancer. Methods: A total of 139 HPV16-positive cervical cancer patients (case group) and 116 HPV16-positive asymptomatic individuals (control group) were enrolle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Variation in the URR region near position 7173 has been previously reported in several studies of cervical cancer. 30,[53][54][55] This region of the URR is postulated to contain multiple binding sites for C/EBPβ 30 and FOXA1. 55 Both C/EBPβ and FOXA1 are transcription factors with important roles in tumorigenesis, [55][56][57][58][59][60][61] and have been shown to regulate HPV16 transcription.…”
Section: Discussionmentioning
confidence: 99%
“…Variation in the URR region near position 7173 has been previously reported in several studies of cervical cancer. 30,[53][54][55] This region of the URR is postulated to contain multiple binding sites for C/EBPβ 30 and FOXA1. 55 Both C/EBPβ and FOXA1 are transcription factors with important roles in tumorigenesis, [55][56][57][58][59][60][61] and have been shown to regulate HPV16 transcription.…”
Section: Discussionmentioning
confidence: 99%
“…The variations T6586C, G6657A and T6850G were identified to be significantly associated with high-grade cervical disease status and could serve as molecular markers of the disease status subject to further validation. Previous studies have also reported the association of LCR variations and cervical disease status [4, 9, 16, 30–33].…”
Section: Discussionmentioning
confidence: 99%
“…The HPV16 genome is divided into three domains, namely, the early region encoding the E1, E2, E4, E5, E6 and E7 genes; the late region encoding the L1 and L2 genes; and the non-coding long control region (LCR) [2][3][4]. The LCR is located between the L1 and E6 genes and comprises approximately 10 % of the viral genome.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays, the sequence analysis of LCR is widely used for the classification of HPV16 DNA into the four major phylogenetic branches (Refs [135][136][137][138][139][140]. Specific intratypic nucleotide polymorphisms have been associated with A4 sub-lineage (A7729C and G7841A), B lineage (G7488A, C7688A, C7763T, C7785T and G7833T), C lineage (A7484C, C7488A, C7668T, C7688A, C7763T, C7785T, G7825A, G7833T, A7836C and G7838G) and D lineage (A7484C, G7488A, C7668T, C7688A, A7728T, T7742G, C7763T and C7785T) (Ref.…”
Section: Long Control Regionmentioning
confidence: 99%